Presence of nucleosomes in plasma and increased thrombin generation in dogs with acute and chronic gastroenteropathies. (March 2021) - Krogh, A.K.H.; Lyngby, J.G.; Bjørnvad, C.R.; Nielsen, L.N.
Abstract: Neutrophil extracellular traps (NETs) which contain nucleosomes protect the host by eliminating extracellular pathogens. However, any inflammatory stimuli can activate NETs and eventually lead to an immune overreaction leading to autoimmune diseases and thrombosis. Acute/chronic gastroenteropathies(aGE/cGE) are prevalent in dogs, and are associated with a strong inflammatory component. The aim of this study was to investigate if dogs with aGE and cGE have increased concentrations of nucleosomes indicative of NETs formation, and whether increased concentrations of nucleosomes are associated with hypercoagulability determined by increased thrombin generation. Twenty-six dogs were enrolled. The dogs were healthy ( n = 11), or presented with aGE( n = 7) or cGE( n = 8). Minimum database including CRP, APTT, PT and fibrinogen, was obtained from all dogs. Citrated plasma was batched and used for subsequent analyses. Nucleosome concentration was analysed using a Cell-Death Detection ELISA-kit and thrombin generation by a calibrated automated thrombogram assay. No statistical differences in nucleosome concentrations were present between the groups. Although a numerically increased concentration of nucleosomes where seen in dogs with aGE(median;range) (0.019 AU;0.003–0.088) and cGE(0.023 AU;0.011–0.256) compared to controls(0.007 AU;0.003–0.042). One dog with GI-lymphoma demonstrated a markedly increased concentration of nucleosomes (0.256 AU). Dogs with aGE showed increased thrombin generation by increased peak ( p = 0.03) and endogenous thrombin potential (p = 0.03); and increased CRP ( p = 0.001), fibrinogen ( p = 0.0002) and prolonged APTT ( p = 0.03) compared to controls. This proof of concept study demonstrates that dogs with aGE and cGE have presence of nucleosomes with marked increase in one dog with GI-lymphoma. Nucleosomes might be linked to haemostatic alterations in dogs with inflammatory and neoplastic diseases. Highlights: Nucleosomes are present in dogs with acute and chronic gastroenteropathies. Dogs with acute gastroenteropathies have an increased endogenous thrombin potential. A dog with neoplasia demonstrated a marked increased concentration of nucleosomes in plasma.